(untitled) (Studia Prawnicze / The Legal Studies, 1985)
The article presents en evolution and legal provisions binding at present concerning abortion in Poland. Special attention. has been paid to the controversies in literature concerning the iscope of admissibility of abortion and limits of penalization. The Polish legislation permits the termination of a pregnancy because of medical, legal and social reasons. Controversies concerned in particular the legality of abortion carried out because of social reasons, which, in practice, constitutes a vast majority of the cases. There were two groups of disputants: supporters and opponents of common admissibility of abortion. The article presents arguments exp.ressed by both the groups. The authors also discussed postulates de lege ferenda which have been recently expressed concerning the changes of provisions of the penal code. The problem has been still; being discussed... The authors support the thoesis on the limitation of admissibility of abortion carried out in view of social reasons.